For the love of humanity : the World Tribunal on Iraq - Çubukçu, Ayça (Pennsylvania studies in human rights., 2018)
Based on two years of fieldwork with the transnational network of antiwar activists who constituted the World Tribunal on Iraq, For the Love of Humanity addresses the contemporary challenges and ambiguities of forging global solidarity through an anti-imperialist politics of human rights and international law.